2012
DOI: 10.3164/jcbn.12-39
|View full text |Cite
|
Sign up to set email alerts
|

Distinct affinity of nuclear proteins to the surface of chrysotile and crocidolite

Abstract: The inhalation of asbestos is a risk factor for the development of malignant mesothelioma and lung cancer. Based on the broad surface area of asbestos fibers and their ability to enter the cytoplasm and nuclei of cells, it was hypothesized that proteins that adsorb onto the fiber surface play a role in the cytotoxicity and carcinogenesis of asbestos fibers. However, little is known about which proteins adsorb onto asbestos. Previously, we systematically identified asbestos-interacting proteins and classified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 43 publications
(38 reference statements)
0
20
0
3
Order By: Relevance
“…Our laboratory demonstrated that the asbestos surface is able to adsorb more than 100 types of different proteins (including proteins such as histones and hemoglobin) as well as DNA and we provided evidence that the asbestos surface can serve as a niche that enhances oxidative modification. Our results revealed the presence of 4-hydroxy-2-nonenal modification and 8-OHdG, respectively, in the proteins and DNA adsorbed to the surface of asbestos fibers [37,60]. These studies all suggest that local excess iron is central to asbestos-induced carcinogenesis.…”
Section: Mechanisms Of Asbestos-induced Carcinogenesis: the Role Of Omentioning
confidence: 52%
“…Our laboratory demonstrated that the asbestos surface is able to adsorb more than 100 types of different proteins (including proteins such as histones and hemoglobin) as well as DNA and we provided evidence that the asbestos surface can serve as a niche that enhances oxidative modification. Our results revealed the presence of 4-hydroxy-2-nonenal modification and 8-OHdG, respectively, in the proteins and DNA adsorbed to the surface of asbestos fibers [37,60]. These studies all suggest that local excess iron is central to asbestos-induced carcinogenesis.…”
Section: Mechanisms Of Asbestos-induced Carcinogenesis: the Role Of Omentioning
confidence: 52%
“…• "Adsorption theory" which tells that the positive or negative charges on the asbestos surface show high affinity for certain nuclear proteins particularly histones and chromatin binding proteins [5] leading to iron concentration in surrounding tissues.…”
Section: Fig 1 Rajsamand and Jodhpur Districts Of Rajasthanmentioning
confidence: 99%
“…15,29,31 For adsorption, asbestos fibers (250 mg/ml) were incubated with membrane fraction proteins (1, 2, 5, 10, 20, 50, 100, 150, and 200 mg/ml) in PBS in a total volume of 1 ml at 37 1C while being shaken at 200 r.p.m. for 30 min.…”
Section: Collection and Analysis Of Asbestos-interacting Membrane Framentioning
confidence: 99%
“…25 The asbestos surface is well known to adsorb proteins. [27][28][29] Therefore, we hypothesized that asbestos fibers without a protein coating may bind to the receptor proteins on the mesothelial cell surface. To identify systematically the proteins involved in the mesothelial endocytosis of asbestos fibers, particularly candidate receptor proteins, we used an LTQ Orbitrap XL mass spectrometry system (Thermo Fisher Scientific, Waltham, MA, USA) combined with a Paradigm MS4 HPLC system (Michrom BioResources, Auburn, CA, USA), and evaluated the candidate proteins using shRNA (short hairpin RNA)-induced knockdown.…”
mentioning
confidence: 99%